PELAKSANAAN KOPERASI KEPADA PIHAK PT. SINDO ARGO DALAM PERJANJIAN ANGKUTAN BUAH SAWIT DI KECAMATAN PARINDU KABUPATEN SANGGAU - NIM. A1012191246, VICTORINO AUDI (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract To use the palm oil fruit transportation agreement service through the Rindu Sawit Cooperative, you can go through the procedure, namely the goods belonging to the oil palm fruit carrier will be weighed to determine the costs to be incurred, for example the carrier sends goods from Sanggau Regency to Pontianak City, the tariff charged is IDR 115,000 / Ton, then the carrier must pay a certain amount of money or shipping costs as stated, then the carrier will obtain a shipping document in the form of a shipping note as proof of delivery. However, in the implementation of the palm oil fruit transportation agreement, the carrier experienced a delay in shipping goods that did not comply with the estimated time set by the Rindu Sawit Cooperative management with the carrier. The delay in shipping oil palm fruit with the agreement on the palm oil fruit transportation agreement between the Rindu Sawit Cooperative and PT. Sindo Argo has been determined that if there is a delay in shipping goods, the service provider will be responsible by reducing the shipping costs. However, in this case, the party blamed by the service user if there is a problem with the delay in shipping goods is the driver. Thus, there needs to be a resolution to the problem of delays between the users of delivery services and the management of the Rindu Sawit Cooperative until the resolution is truly completed in accordance with the agreement of both parties. The research problem is: